Cognitive Function in Patients With Complex Regional Pain Syndrome (CRPS) - Liesto, Sanna; Aho, Tommi; Jääskeläinen, Satu K.; Hietanen, Marja; Kalso, Eija (Wiley, 2025)
Background: Complex Regional Pain Syndrome (CRPS) is characterised by pain, sensory, vasomotor, sudomotor, motor, and trophic symptoms, with cognitive symptoms also reported. This study aimed to examine the neuropsychological profile of patients with meticulously diagnosed CRPS 1 and 2.
Methods: A neuropsychological examination was conducted in 54 CRPS patients. The test battery included Block Design and Similarities from Wechsler Adult Intelligence-IV, word list learning and delayed recall, and Digit Span from Wechsler Memory Scale-III, Trail Making Test (TMT), verbal and drawing fluency, Brixton, Manikin and Bourdon-Wiersma tests. Patients performing below -0.67 SD of the performance of a healthy Finnish population in ≥ 3 tests were classified as having cognitive decline. Questionnaires included Insomnia Severity Index, Beck Depression Inventory-II, CRPS Severity Scale, Disabilities of the Arm, Shoulder and Hand, Pain Catastrophizing Scale, Resilience Scale-14, Brief Pain Inventory, Insomnia Severity Index and State Trait Anxiety Inventory. Patients were asked about subjective cognitive difficulties.
Results: A subgroup comprising 30% of the CRPS patients showed cognitive decline. Higher pain catastrophising was associated with poorer test performance in TMT Part A. There were no differences between left and right sides on the visual attention test. Subjective cognitive difficulties were not associated with objective cognitive test performance. Cognitive functioning did not differ between CRPS 1 and 2 patients.
Conclusions: This study elucidates how CRPS affects cognitive functioning, important information when tailoring multidisciplinary rehabilitation to CRPS patients. Psychological factors may have a stronger impact on subjective cognitive difficulties than on objective test performances.
Significance statement: CRPS is an enigmatic syndrome with multifactorial origins, leading to chronic, disabling pain due to progressing neuroplastic alterations in the central nervous system. This study adds comprehensive novel information about cognitive function in CRPS, as, except for lateralised cognitions and body perception, cognitive domains have not previously been extensively studied in CRPS patients. Cognitive decline in 30% of patients indicates that neuropsychological assessment should be included in the diagnostics, and results considered in the rehabilitation of CRPS patients.
Trial registration: ClinicalTrials.gov identifier: NCT04439669